Construction of Islamic Character Education through Narrative Algorithms in the Novel Janji by Tere Liye - Mohammad Rozaq; Fathi Hidayah; Jon Iskandar Bahari (Journal of Educational Management Research, 2026)
This study is based on the importance of character education in responding to moral challenges in contemporary society and the potential of literary works as a medium for internalizing Islamic values. Previous studies on Janji by Tere Liye generally focused on identifying character values, while the narrative mechanism underlying character formation has received limited attention. Therefore, this study aims to analyze the narrative algorithm of Islamic character education through the transformation of Bahar’s character in the novel Janji. The research employed a qualitative approach with a library research design. Data were collected through documentation techniques from the novel Janji and relevant academic literature, then analyzed using the Miles, Huberman, and Saldaña model, including data condensation, data display, and conclusion drawing. The findings reveal three stages of the narrative algorithm: moral degradation, moral reconstruction, and character crystallization. Bahar’s transformation develops through experiences of guilt, suffering, repentance, and social responsibility, ultimately producing a morally mature character who positively influences society. This study concludes that Islamic character education in literature is constructed through a gradual narrative process. The study contributes theoretically by introducing a narrative algorithm perspective and practically by strengthening the use of literary works as media for Islamic character education.